2007
DOI: 10.1158/1535-7163.mct-06-0372
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of major vault protein increases doxorubicin sensitivity and nuclear accumulation and disrupts its sequestration in lysosomes

Abstract: The major vault protein (MVP) is the major constituent of the vault particle, the largest known ribonuclear protein complex. To date, vaults have no clear function, although their low expression levels in de novo chemosensitive and curable tumors, such as testicular cancer, make them attractive candidates as contributors to intrinsic drug resistance. Here, we show that MVP knockdown in human bladder cancer cells via small interfering RNA results in sensitization toward doxorubicin in two distinct exposure prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 46 publications
2
61
1
1
Order By: Relevance
“…The membrane fractions were checked for the fractionation purification by immunoblotting for the cytosolic and membrane markers ␣-tubulin (Calbiochem) and Caveolin-1 or integrin ␤1 (BD Biosciences), respectively. UMUC3 cells were transiently transfected with pFLAG-CMV4 and pFLAG-CMV4-RhoGDI2, and mass spectrometry analysis of the immunoprecipitate was carried out as described previously (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…The membrane fractions were checked for the fractionation purification by immunoblotting for the cytosolic and membrane markers ␣-tubulin (Calbiochem) and Caveolin-1 or integrin ␤1 (BD Biosciences), respectively. UMUC3 cells were transiently transfected with pFLAG-CMV4 and pFLAG-CMV4-RhoGDI2, and mass spectrometry analysis of the immunoprecipitate was carried out as described previously (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…MVP/vaults have been associated with multidrug resistance (21)(22)(23), nuclear-cytoplasmic transport (24), innate immunity (25), autophagy (26), and signal transduction pathways (27)(28)(29)(30)(31); however, the precise function of MVP/ vault remains enigmatic. Our previous work indicating MVPinduced type I IFN production upon hepatitis C virus infection uncovers a new role of MVP in modulating innate immunity during viral infection (32).…”
mentioning
confidence: 99%
“…In 2007 it was shown that knockdown of the major vault protein (MVP) using siRNA disrupted lysosomal uptake of not only doxorubicin, but also the intracellular pH probe LysoSensor and the lysosomal specific antigen LAMP1. This study indicated that MVP was integral in redistributing the drug away from the nucleus to the lysosomes (Herlevsen et al, 2007). In another study, cells were exposed to various weak bases before lysosomes were isolated and their contents quantified using high performance liquid chromotography.…”
Section: Drug Sequestration Through the Endosomal Pathwaysmentioning
confidence: 90%